A Study of E-Waste Disposal Management Awareness among Local Community based on KAP Model - Tukiman, Noor Fatin Izatie; Mustaffa, Siti Aisyah (Research in Management of Technology and Business, 2021)
E-waste is a trash generated by abandoned gadgets and components, as well as by chemicals utilised in the production or use of personal products. The reduction in the creation of e-waste contributes to the preservation of resources and reduction of the quantity of energy from the earth causing pollution and damaging long-lasting health without adequate management or management of trash. The awareness of society is the fundamental foundation for overcoming this problem. In this study, the degree of knowledge, attitude and practice in managing e-waste disposal is determined and the link between factors is examined. The research consisted of 160 respondents from the area of Tebrau, Johor Bahru. For this study, the quantitative approach was used as an instrument for obtaining input from respondents. Data examined using SPSS software system for interpretation of information through descriptive and correlation analyses. Knowledge, attitude and practices of e-waste disposal management are the factors considered in this study. The results of the study showed that the individual with better knowledge and an e-waste disposal attitude seems to have good practice as well. These findings might offer reference information on e-waste management in Malaysia and the development of effective e-waste management program by researchers and other stakeholders.